Edukasi Pengendalian Gaya Hidup pada Penderita Penyakit Tidak Menular di Puskesmas Putri Ayu Kota Jambi - Yuliana, Yuliana; Nurfitriani, Nurfitriani; Pebrianti, Dwi Kartika (3031-8572, 2024)
Non-communicable diseases (NCDs) are known as chronic diseases but are not transmitted from person to person. The World Health Organization (WHO) predicts that in 2020 non-communicable diseases will be the cause of 73% of deaths in the world (Isa, 2017). Non-communicable diseases consist of asthma, chronic obstructive pulmonary disease (COPD), cancer, diabetes mellitus (DM), hyperthyroidism, hypertension, coronary heart disease (CHD), heart failure, stroke, chronic kidney failure, kidney stone disease and joint disease or rheumatism. Around 80% of all NCD deaths occur in low-income countries (Riau Provincial Health Office, 2019). Some factors that trigger non-communicable diseases are behavioral factors such as smoking, alcohol consumption, lack of physical activity, fast food, lack of fruit and vegetable consumption, this is certainly a trigger for a person's physiological health. Community Service was carried out at the Putri Ayu Health Center which is a partner location of PkM STIKBA Jambi, the implementing team provided education to participants, the next activity the team provided leaflets. The team also provided questionnaires for pre and post, the results obtained an average knowledge of participants with a value of 4.4 and the results of the post with an average value of 6.3. from these results, an increase in knowledge was obtained after being educated. It is expected that the Putri Ayu Health Center, especially in the general polyclinic, will provide education to the community about non-communicable diseases